Preparation method of Pyro-MEMS (Micro-Electro-Mechanical System) micro-charging film based on energetic ink spin-coating process
Preparation of Pyro-MEMS micro-charge films through spin coating technology based on energy-containing inks has solved the problem of complex charging methods of traditional pyro-MEMS products and incompatible with MEMS systems, and achieved simple operation, uniform and dense film, and easy to regulate thickness. The effect has improved the compatibility and development potential of pyrotechnology.
Patent Information
- Application Number
- CN202411635986.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
AI Technical Summary
The traditional pyrotechnic charging method is complex in operation and consumes a lot of manpower and material resources. The pyrotechnic agent is powdery and cannot meet the needs of miniaturization. It has poor compatibility with the MEMS system, which limits the development of pyrotechnic technology.
Using the Pyro-MEMS micro-charge film preparation method based on the energy-containing ink spin coating process, stable Al/Co3O4/Double 5-AT/NC or B is formed through copper substrate pretreatment, ink preparation and spin coating film formation. /KNO3/5-AT/NC energy-containing film.
The simplicity of the preparation process and the convenience of operation are achieved. The prepared energy-containing film is uniform and dense, and the thickness is easy to regulate. It is suitable for the needs of MEMS systems, and the compatibility and development potential of pyrotechnology are enhanced.
Smart Images

Figure CN119456365A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of micro-charges, and in particular is a method for preparing a Pyro-MEMS micro-charge film based on an energetic ink spin coating process. Background Art
[0002] Pyrotechnics are a general term for disposable components and devices that are filled with gunpowder or explosives and produce combustion or explosion after being stimulated by external energy, used to ignite gunpowder, detonate explosives, perform mechanical work or produce special effects. Pyrotechnics and pyrotechnics can reflect the development level of a country in all aspects. Today, pyrotechnics have extremely high strategic value.
[0003] Pyrotechnic devices have the advantages of small size, light weight and good reliability, so they have a wide range of applications. For example, in the civilian field, they are used in airbags, engineering blasting, deep well oil production, ore mining, etc. They can also be used in medical treatment to remove stones in the human body by micro-blasting.
[0004] In today's era, with the development of the times, the performance requirements for pyrotechnics are also increasing. The development of micro-pyrotechnics with low-energy ignition and high-energy output is a research goal that all countries in the world are striving to pursue. By combining miniaturized, digitalized and intelligent micro-electromechanical systems (MEMS) with pyrotechnic technology, the structural miniaturization, system integration and functional dexterity of MEMS pyrotechnics can be achieved. In MEMS pyrotechnics, the performance of the pyrotechnic agent directly determines its ignition ability. However, the traditional charging method (pressing, injection, etc.) is complicated to operate and consumes a lot of manpower and material resources. The pyrotechnic agent is in powder form, which not only cannot meet the miniaturization requirements, but also has poor compatibility with MEMS systems, which restricts the development of pyrotechnic technology. Therefore, seeking pyrotechnic agents and charging processes compatible with MEMS chips is of great significance to the development of pyrotechnics. Summary of the invention
[0005] The purpose of the present invention is to solve the problems existing in the above-mentioned prior art and to provide a method for preparing a Pyro-MEMS micro-charge film based on an energetic ink spin coating process.
[0006] The present invention is achieved through the following technical solutions: A method for preparing a Pyro-MEMS micro-charge film based on an energetic ink spin coating process comprises the following steps: 1) Substrate pretreatment: Place the copper substrate in a 40% nitric acid solution for 30 s to remove the oxide film on the surface of the copper substrate, then rinse with a large amount of deionized water and dry naturally for use.
[0007] 2) Ink preparation: First, nitrocellulose was added to acetone solvent and ultrasonically treated for 20 min to completely dissolve the nitrocellulose in acetone; secondly, Al / Co3O4 / double 5-AT powder or B / KNO3 / 5-AT powder was added to the above solution and stirred and ultrasonically treated to make the solution fully uniform to obtain Al / Co3O4 / double 5-AT / NC energetic ink or B / KNO3 / 5-AT / NC energetic ink.
[0008] 3) Spin coating: Place the copper substrate on a spin coater and drop the prepared Al / Co3O4 / double 5-AT / NC energetic ink or B / KNO3 / 5-AT / NC energetic ink onto the copper substrate rotating at a low speed.
[0009] 4) Diffusion and volatilization: Under the high-speed rotation of the coating machine, the Al / Co3O4 / double 5-AT / NC energetic ink or the B / KNO3 / 5-AT / NC energetic ink diffuses from the middle of the copper substrate to the surrounding area and covers the entire copper substrate; during the diffusion process, accompanied by the volatilization of acetone, a stable Al / Co3O4 / double 5-AT / NC energetic film or B / KNO3 / 5-AT / NC energetic film is finally formed.
[0010] As a preferred technical solution, in step 2), the mass ratio of the substances in the Al / Co3O4 / double 5-AT / NC energetic ink is Al / Co3O4:double 5-AT:NC=70:20:10, and the mass ratio of the substances in the B / KNO3 / 5-AT / NC energetic ink is B / KNO3:5-AT:NC=80:10:10.
[0011] As a preferred technical solution, in step 2), in the Al / Co3O4 / double 5-AT / NC energetic ink, the mass of Al is 0.25g, the mass of Co3O4 is 0.836g, the mass of double 5-AT is 0.310g, and the mass of NC is 0.155g; in the B / KNO3 / 5-AT / NC energetic ink, the mass of B is 0.27g, the mass of KNO3 is 0.73g, the mass of 5-AT is 0.125g, and the mass of NC is 0.125g.
[0012] As a preferred technical solution, in step 2), during the preparation of Al / Co3O4 / double 5-AT / NC energetic ink, the volume of acetone added is 12 mL; during the preparation of B / KNO3 / 5-AT / NC energetic ink, the volume of acetone added is 12 mL.
[0013] As a preferred technical solution, in step 3), the amount of Al / Co3O4 / double 5-AT / NC energetic ink or B / KNO3 / 5-AT / NC energetic ink added is 5 to 7 drops.
[0014] As a preferred technical solution, in step 4), the high-speed rotation speed of the glue-spinning machine is 3.20 kr·min -1 ~3.56kr·min -1 .
[0015] As a preferred technical solution, in step 4), the rotation time of the glue spreader is 20 s.
[0016] As a preferred technical solution, in step 3), the amount of Al / Co3O4 / double 5-AT / NC energetic ink added is 5 drops, and the amount of B / KNO3 / 5-AT / NC energetic ink added is 7 drops.
[0017] As a preferred technical solution, in step 4), for Al / Co3O4 / double 5-AT / NC energetic ink, the high-speed rotation speed of the coating machine is 3.20 kr·min -1 ; For B / KNO3 / 5-AT / NC energetic ink, the high speed rotation speed of the coating machine is 3.56kr·min -1 .
[0018] Compared with the prior art, the method of the present invention has the following beneficial effects: ① The preparation process is simple, the operation is convenient, the preparation process is efficient, and it is conducive to engineering application; ② The prepared energetic film is uniform and dense, and the thickness of the energetic film is easy to control. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. The drawings herein are used to provide further explanation of the present invention and constitute a part of this application. The schematic embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation on the present invention.
[0020] Figure 1 Planar SEM images and EDS images of B / KNO3 / 5-AT / NC energetic films with different ink ratios.
[0021] Figure 2 Different substrates and their SEM images, as well as different substrates coated with B / KNO3 / 5-AT / NC energetic ink and their SEM images.
[0022] Figure 3 Surface SEM images, cross-sectional SEM images and EDS images of films with different thicknesses when B / KNO3:5-AT:NC=80:10:10.
[0023] Figure 4SEM images of pure copper sheet, Al / Co3O4 / double 5-AT / NC film sample, Al / Co3O4 / double 5-AT / NC film, SEM image of Co3O4, SEM image of double 5-AT and SEM image of Al powder.
[0024] Figure 5 Planar SEM images and EDS images of Al / Co3O4 / double 5-AT / NC energetic films at different ink ratios.
[0025] Figure 6 Surface SEM images, cross-sectional SEM images and EDS images of films with different thicknesses when Al / Co3O4:double 5-AT:NC=70:20:10.
[0026] Figure 7 XRD patterns of raw materials and thin film samples when B / KNO3:5-AT:NC=80:10:10.
[0027] Figure 8 FT-IR spectra of raw materials and film samples when B / KNO3:5-AT:NC=80:10:10.
[0028] Fig. 9 XRD patterns of raw materials and thin film samples when Al / Co3O4:double 5-AT:NC=70:20:10.
[0029] Fig.10 FT-IR spectra of raw materials and film samples when Al / Co3O4:double 5-AT:NC=70:20:10.
[0030] Fig.11 DSC spectra of energetic films with different ratios of B / KNO3 / 5-AT / NC.
[0031] Fig.12 TG spectra of energetic films with different ratios of B / KNO3 / 5-AT / NC.
[0032] Fig.13 DSC spectra of Al / Co3O4 / double 5-AT / NC energetic films with different ratios. DETAILED DESCRIPTION
[0033] The embodiments of the technical solution of the present invention will be described in detail below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and the protection scope of the present invention cannot be limited thereto. It should be noted that, unless otherwise specified, the technical terms or scientific terms used in this application should be the common meanings understood by those skilled in the art to which the present invention belongs. Example 1
[0034] A method for preparing a Pyro-MEMS micro-charge film based on an energetic ink spin coating process comprises the following steps: 1) Substrate pretreatment: Place the copper substrate in a 40% nitric acid solution for 30 s to remove the oxide film on the surface of the copper substrate, then rinse with a large amount of deionized water and dry naturally for use.
[0035] 2) Preparation of ink: First, add 12 mL of acetone to the nitrocellulose and perform ultrasonic treatment for 20 min to completely dissolve the nitrocellulose in the acetone; secondly, add B / KNO3 / 5-AT powder to the above solution and perform stirring and ultrasonic treatment to make the solution fully uniform to obtain B / KNO3 / 5-AT / NC energetic ink; the mass ratio of the substances in the B / KNO3 / 5-AT / NC energetic ink is B / KNO3:5-AT:NC=80:10:10, wherein the mass of B is 0.27 g, the mass of KNO3 is 0.73 g, the mass of 5-AT is 0.125 g, and the mass of NC is 0.125 g.
[0036] 3) Spin coating: Place the copper substrate on a spin coater and add 7 drops of the prepared B / KNO3 / 5-AT / NC energetic ink onto the copper substrate rotating at a low speed.
[0037] 4) Diffusion and volatilization: Adjust the rotation speed of the glue machine to 3.56 kr·min -1 , the rotation time is 20 s. During this period, the B / KNO3 / 5-AT / NC energetic ink diffuses from the middle of the copper substrate to the surrounding areas and covers the entire copper substrate. During the diffusion process, accompanied by the volatilization of acetone, a stable B / KNO3 / 5-AT / NC energetic film is finally formed. Example 2
[0038] A method for preparing a Pyro-MEMS micro-charge film based on an energetic ink spin coating process comprises the following steps: 1) Substrate pretreatment: Place the copper substrate in a 40% nitric acid solution for 30 s to remove the oxide film on the surface of the copper substrate, then rinse with a large amount of deionized water and dry naturally for use.
[0039] 2) Ink preparation: First, 12 mL of acetone was added to the nitrocellulose and ultrasonically treated for 20 min to completely dissolve the nitrocellulose in the acetone; secondly, Al / Co3O4 / double 5-AT powder was added to the above solution and stirred and ultrasonically treated to make the solution fully uniform to obtain Al / Co3O4 / double 5-AT / NC energetic ink; the mass ratio of the substances in the Al / Co3O4 / double 5-AT / NC energetic ink was Al / Co3O4:double 5-AT:NC=70:20:10, wherein the mass of Al was 0.25 g, the mass of Co3O4 was 0.836 g, the mass of double 5-AT was 0.310 g, and the mass of NC was 0.155 g.
[0040] 3) Spin coating: Place the copper substrate on a spin coater and drop 5 drops of the prepared Al / Co3O4 / double 5-AT / NC energetic ink on the copper substrate rotating at a low speed.
[0041] 4) Diffusion and volatilization: Adjust the rotation speed of the glue machine to 3.20kr·min -1 , the rotation time is 20 s. During this period, the Al / Co3O4 / double 5-AT / NC energetic ink diffuses from the middle of the copper substrate to the surrounding areas and covers the entire copper substrate. During the diffusion process, accompanied by the volatilization of acetone, a stable Al / Co3O4 / double 5-AT / NC energetic film is finally formed.
[0042] The following is a further analysis of the relevant products involved in the preparation method of the embodiment of the present invention, and the specific results are as follows: 1. Test characterization Scanning electron microscopy (SEM) was used to explore the advantages of spin coating process, which has controllable thickness and can be formed on different substrates. X-ray diffraction (XRD) and infrared spectroscopy (FT-IR) were used to determine the composition of the prepared energetic film samples to confirm the correctness of the process.
[0043] 1.1 Morphology analysis 1.1.1 Morphology analysis of B / KNO3 / 5-AT / NC energetic films The prepared B / KNO3 / 5-AT / NC energetic film samples were analyzed by SEM and EDS. Figure 1 As shown, Figure 1 Figures ad are the plane SEM images of a film when the ink ratio B / KNO3:5-AT:NC=80:10:10, 70:20:10, 60:30:10, and 90:0:10; a1-d1 are the EDS images of films with different ratios. The film is dark brown, with no obvious cracks on the surface, and is flat and dense.
[0044] from Figure 1It can be clearly seen in a that the film is mainly a fiber network structure, which is composed of the raw material B powder in the shape of a prism and the 5-AT in the shape of a spherical KNO3 with a diameter of about 2 μm connected together by nitrocellulose (NC). The surface morphology of the films of other proportions is not significantly different from that of a.
[0045] In order to further determine the composition of the film, EDS spectra were used to detect the distribution and proportion of various elements in film samples with different proportions. Figure 1 As shown in a1-d1), the distribution of each element in the film is dotted, and it can be intuitively seen from the spectrum that the film is composed of elements B (red), K (yellow), N (blue), O (purple), and C (green). Various elements are densely and randomly evenly distributed on the copper substrate, which shows that various raw materials are evenly distributed on the film obtained by the process of the present invention, and there is less agglomeration, which is beneficial to improve the heat release performance of the ignition powder. It can be seen from the energy spectrum of the film that when the ratio of B / KNO3:5-AT:NC is 90:0:10, the contents of B, K, N, O, and C are 26.52%, 27.35%, 10.23%, 32.51%, and 3.29%, respectively, which are basically similar to the theoretical content. As the ratio of B / KNO3 decreases, the contents of elements B and K decrease. The above phenomenon preliminarily shows that it is feasible and successful to prepare films with different proportions.
[0046] In order to explore the film formation of ink on different substrates through spin coating process, SEM analysis was carried out on different substrates and film samples. The results are as follows Figure 2 As shown, Figure 2 (a)-(d) are copper substrate, PCB, quartz glass, and ceramic glass substrate respectively; (a1)-(d1) are SEM images of different substrates; (a2)-(d2) are samples of different substrates coated with ink; (a3)-(d3) are SEM images of different substrates coated with ink. Figure 2 In a, a1 and b, b1, the pure copper sheet and pure PCB board are bright yellow, with a flat surface and metallic luster; Figure 2 As shown in c and c1, pure quartz glass is translucent and has a flat surface; Figure 2 As shown in d and d1, pure ceramic glass is milky white, and its SEM image shows that its surface is composed of many irregular blocky substances interlaced, and the surface is uneven. Figure 2 It can be seen from a2-d2 that the ink composed of B / KNO3 / 5-AT / NC is evenly spin-coated on various substrates, with good film-forming effect, dark brown film, relatively rough surface, and the surface SEM images of films on different substrates are not much different, all of which are formed by various different substances interlaced in a fiber network. Therefore, it is shown that the film prepared by the spin coating process of the present invention has good compatibility on different substrates.
[0047] SEM and EDS analysis were performed on films of different thicknesses. Figure 3 As shown, Figure 3 ac are the surface SEM images of the one-layer, two-layer and three-layer films when B / KNO3:5-AT:NC=80:10:10; a1-c1 are the cross-sectional SEM images of films with different thicknesses; a2-c2 are the EDS layering images of the cross-sectional films with different thicknesses. ac are the surface SEM images of the one-layer, two-layer and three-layer films when the B / KNO3:5-AT:NC ratio is 80:10:10. With the increase of thickness, the morphology of the film surface does not change significantly; from a1-c1, it can be seen that the thickness of the one-layer film is 8 μm, the thickness of the two-layer film is 25 μm, and the thickness of the three-layer film is 83 μm, which proves that it is feasible and successful to prepare films of different thicknesses. However, the thickness increase of films of different thicknesses is different, which may be because the surface of the pure substrate is relatively smooth. Compared with the surface coated with the film, the pure substrate has poor adhesion to the ink. The good adhesion between the ink and the ink increases the thickness of the film. The three-layer film has a small amount of shedding of the lower substrate and the upper ink, which may be because the upper ink has relatively good adhesion, and the strong centrifugal force will throw off the relatively less adhesive substrate and film layer; a2-c2 are EDS layered diagrams of films of different thicknesses. The elements O, K, B, C, N, and Cu are evenly distributed on the film, proving that the dispersion of various substances is good. Therefore, changing the amount of ink drops can control the thickness of the film.
[0048] 1.1.2 Morphology analysis of Al / Co3O4 / double 5-AT / NC energetic films The morphology and composition elements of Al / Co3O4 / double 5-AT / NC energetic films and their components were detected by SEM and EDS. The results are as follows Figure 4 As shown, Figure 4 In the figure, a is a pure copper sheet; b is an Al / Co3O4 / double 5-AT / NC thin film sample; c is the SEM of Al / Co3O4 / double 5-AT / NC thin film; d is the SEM of Co3O4; e is the SEM of double 5-AT; f is the SEM of Al powder.
[0049] like Figure 4As shown in a of [reference], the pure copper sheet is bright yellow, with a flat surface and metallic luster. After the spin-coating process, the ink is spin-coated onto the copper substrate, and the surface of the copper substrate becomes black, matching the color of the ink. d, e, and f are the SEM images of the raw materials Al powder, Co3O4, and bis-5-AT that make up the ink, respectively. The raw material particles all reach the nanoscale, which is beneficial for ignition. c is the SEM image of the energetic film sample of Al / Co3O4:bis-5-AT:NC = 80:10:10. It can be clearly seen from the figure that the surface of the film is uneven, and spherical nano-Al powder, nano-Co3O4 particles, and nano-bis-5-AT particles can be directly distinguished. Moreover, the three types of particles are relatively evenly distributed and there is less agglomeration phenomenon, indicating that the Al / Co3O4 / bis-5-AT / NC energetic film has been successfully prepared and the film-forming effect is good.
[0050] Figure 5 a-d of [reference] are the planar SEM images of the films of Al / Co3O4:bis-5-AT:NC = 70:20:10, 60:30:10, 80:10:10, and 90:0:10, respectively. It can be seen from the figure that the various raw material particles are interlaced with each other, and the SEM images of the films with different ratios are not very different. Figure 5 a1-d1 of [reference] are the EDS images of the films with different ratios. It can be seen that the film is composed of elements C (yellow), Al (red), O (blue), Co (green), and N (purple), and the distribution of various elements is dense and uniform. As Figure 5 As shown in b1 of [reference], when Al / Co3O4:bis-5-AT:NC = 60:30:10, the mass fractions of various elements are 18.29% (C), 15.34% (N), 14.92% (O), 14.35% (Al), 37.10% (Co), and 0 (Cu). The film does not contain the element Cu of the copper substrate, indicating that the ink completely covers the substrate. Moreover, as the content of Al / Co3O4 increases, the contents of Al and Co increase significantly. The above phenomena indicate that the raw material substances are evenly distributed and the films with different ratios are successfully prepared.
[0051] SEM and EDS were used to analyze the films with different thicknesses, and the charge loading of the films with different thicknesses was counted. The results are as Figure 6 shown in Table 1. Figure 6 a-d of [reference] are the planar SEM images of one-layer, two-layer, three-layer, and four-layer films when Al / Co3O4:bis-5-AT:NC = 70:20:10. By observing their morphologies, the morphologies of the surfaces of the films with different thicknesses are not very different. Figure 6a1-d1 are cross-sectional SEM images of films with different thicknesses. It can be seen from the figure that the thickness of the first film is about 10 μm, the thickness of the second film is about 23 μm, the thickness of the third film is about 38 μm, and the thickness of the fourth film is about 55 μm. It can be seen from Table 1 that starting from the second layer, the increase in the amount of film loading is roughly the same, which is more than the increase in the first layer. The reason for this may be that the adhesion of the film surface is better than that of the copper substrate, which is more conducive to the deposition of ink. The third and fourth film layers fall off. The possible reason is that the viscosity between inks is greater than that between substrates and inks, which may cause the substrate and ink to separate under high-speed rotation. Figure 6 a2-d2 are cross-sectional EDS images of films with different thicknesses. By comparing the element contents of films with different thicknesses, it is found that with the increase of thickness, the proportions of various elements are not much different, which means that various substances are evenly distributed on the film.
[0052] Table 1 Charge amount of films with different thicknesses
[0053] 1.2 Component Analysis 1.2.1 Composition analysis of B / KNO3 / 5-AT / NC energetic films In order to determine the composition of various raw materials and film samples in the experiment, the present invention performs X-ray diffraction (XRD) analysis on the raw materials and a film of B / KNO3:5-AT:NC=80:10:10, and the spectrum is as follows Figure 7 As shown in the figure, (a) B powder; (b) NC; (c) KNO3; (d) 5-AT; (e) B / KNO3 / 5-AT / NC energetic film; (f) copper substrate.
[0054] Figure 7The spectrum a of the raw material B powder does not show diffraction peaks, mainly because the B powder used in the experiment is amorphous B powder, and the arrangement of its internal atoms is not periodic. Since the raw material NC is an amorphous polymer, its spectrum b and the thin film sample spectrum e do not show corresponding diffraction peaks. Spectrum e corresponds to the XRD curve of the thin film sample. The three relatively strong diffraction peaks (43.4°, 50.4°, and 74.4°) of this curve correspond to the three diffraction peaks of spectrum f of the copper substrate, which may be caused by the film being not thick enough. The diffraction peaks of 2θ at 19.0°, 23.6°, 29.4°, 32.5°, 33.9°, 41.5°, and 46.8° match the crystal planes (110), (021), (012), (102), (112), (041), and (023) in spectrum c of KNO3 (JCPDS04-0787), indicating that the film contains KNO3. The diffraction peaks of the spectrum e curve at 13.7°, 22.8°, 24.4°, 28.2°, 29.5°, 30.7°, and 33.4° match those of the raw material 5-AT (JCPDS 23-1513) corresponds to the main diffraction peak in spectrum d, indicating that the film contains 5-AT. The above results show that the B / KNO3 / 5-AT / NC energetic film sample was successfully prepared.
[0055] In order to further determine the composition of the prepared film samples, FT-IR spectroscopy analysis was also performed on the raw material components and the film. Figure 8 As shown in the figure, (a) B powder, (b) NC, (c) KNO3, (d) 5-AT, and (e) B / KNO3 / 5-AT / NC energetic film.
[0056] like Figure 8 As shown in the figure, curve a is boron powder, which has no functional groups on its surface, so the curve has almost no absorption peak. In the NC spectrum of curve b, 1640 cm -1 , 1270 cm -1 The absorption peaks at 734 cm-1 are due to the asymmetric stretching vibration and symmetric stretching vibration of -ONO2. -1 The absorption peak at 1070 cm -1 、997cm -1 、817 cm -1 The absorption peak at is caused by the stretching vibration of COC in the cellulose skeleton. In the spectrum of curve c, the diffraction peak is 2400 cm -1 、1460 cm -1 、1372cm -1 、852 cm -1Corresponding to the stretching vibration peak of the anion in KNO3. In addition, in the spectrum shown in curve d, we can see the peaks between 3180 and 3480 cm -1 There is an obvious absorption peak at 1635 cm -1 and 1160 cm -1 The positions of -NH2 and NH show the shear vibration characteristics, 1062 cm -1 and 756 cm -1 The absorption peak at 3180-3480 cm corresponds to the skeleton stretching vibration of the 5-AT tetrazole ring. Compared with curve e and other curves, the absorption peak at 3180-3480 cm does not appear due to the relatively low content of 5-AT. -1 The corresponding stretching vibration peak of -NH2, but the absorption peaks corresponding to most of the raw materials can be found on curve e, thus proving that the B / KNO3 / 5-AT / NC energetic thin film sample was successfully prepared.
[0057] 1.2.2 Composition analysis of Al / Co3O4 / double 5-AT / NC energetic films The composition of Al / Co3O4 / double 5-AT / NC energetic films and their various raw materials were determined by XRD measurement, such as Fig. 9 As shown in the figure, (a) Al powder, (b) NC, (c) double 5-AT, (d) Co3O4, (e) Al / Co3O4 / double 5-AT / NC energetic film, and (f) copper substrate. Fig. 9In the figure, curve b is the XRD curve of NC, which has no obvious diffraction peaks. The main reason is that nitrocellulose is an amorphous material, so no diffraction peaks of nitrocellulose are observed in curve e. The diffraction peaks of curve e at 12.5°, 15.4°, 19.6°, 21.1°, 23.1°, 24.9°, 27.6°, and 29.1° correspond to the diffraction peaks of XRD curve c of double 5-AT. The diffraction peaks of curve e at 38.4°, 44.6°, and 65.1° correspond to the (100), (200), and (220) crystal planes in Al powder (JCPDS 04-0787), respectively. In addition, the diffraction peaks of curve e at 2θ of 31.3°, 36.9°, 44.8°, 59.5°, and 65.3° correspond to the (220), (311), (400), (511), and (400) planes of Co3O4 standard spectrum (JCPDS 43-1003), respectively. In addition, curve e has diffraction peaks at 43.3°, 50.4°, and 74.1°, which match the diffraction peaks of copper substrate (JCPDS 04-0836), which may be caused by the thin film. The above results prove that the film samples contain Al powder, double 5-AT, and Co3O4, which means that the Al / Co3O4 / double 5-AT / NC energetic film was successfully prepared.
[0058] In order to further determine the composition of the prepared film samples, FT-IR spectroscopy was also performed, such as Fig.10 As shown in the figure, (a) Al powder, (b) NC, (c) double 5-AT, (d) Co3O4, (e) Al / Co3O4 / double 5-AT / NC energetic film, (e) NC. Since there is no functional group in the structure of nano-Al powder, there is no obvious infrared absorption peak in its FT-IR spectrum curve e. In the NC spectrum of curve a, 1635 cm -1 , 1270 cm -1 The absorption peaks at 742 cm-1 correspond to the asymmetric stretching vibration and symmetric stretching vibration of -ONO2. -1 The absorption peak at 1070 cm -1 、997cm -1 、817 cm -1 The absorption peak at 1450 cm is caused by the stretching vibration of COC in the cellulose skeleton. -1 Corresponding to the stretching vibration of N=N double bond, 3450 cm -1 The stretching vibration peak corresponding to the NH bond is 1290 cm -1 Corresponding to the stretching vibration of the NN bond, 739 cm -1 and 812 cm -1Corresponding to the out-of-plane deformation vibration of the NH bond, 1640 cm -1 and 1550 cm -1 Corresponding to the stretching vibration peak of the C=N double bond. Curve c represents the infrared spectrum of the raw material Co3O4, at 658.5 cm -1 and 549.2 cm -1 Corresponding to the stretching vibration of Co-O bond. Due to the low content of double 5-AT, there is no 3450 cm -1 However, in curve d, the absorption peaks corresponding to various raw materials can basically be found, which indicates that the Al / Co3O4 / double 5-AT / NC energetic film is successfully prepared.
[0059] 2. Exothermicity of B / KNO3 / 5-AT / NC energetic films In nitrogen atmosphere, the thermal properties of samples scraped from B / KNO3 / 5-AT / NC energetic films with different ratios were analyzed at a heating rate of 10 K / min, a gas flow rate of 30 ml / min, and a temperature range of 100-600 °C. The curves are shown in Figure 2. Fig.11 and Fig.12 shown. Fig.11 and Fig.12 The middle curves a are all B / KNO3:5-AT:NC=100:0:0; b are all B / KNO3:5-AT:NC=90:0:10; c are all B / KNO3:5-AT:NC=80:10:10; d are all B / KNO3:5-AT:NC=70:20:10; e are all curves of thin film samples with B / KNO3:5-AT:NC=60:30:10.
[0060] Fig.11 All the curves in the graph show endothermic peaks at 135.11 ℃ and 330.61 ℃, corresponding to the crystal transformation (diamond to triangle) and melting of KNO3, which is consistent with the DSC curve of KNO3. Fig.11 A and Fig.12 From a, we can see that powder B reacts with molten KNO3 at 480-530 ℃ to generate KBO2 and NO, and the sample loses a lot of mass and releases a lot of heat. The thermal decomposition of NC is independent of the main reaction process, such as Fig.11 b and Fig.12 As shown in b, compared with the ignition powder without NC Fig.11 Curve a shows that the film sample has an obvious exothermic peak at 207.50 ℃, which mainly corresponds to the thermal decomposition curve of NC. The main reaction mass loss of B / KNO3 is between 450-500 ℃, and the main reaction temperature is advanced by 57.3 ℃, which indicates that the addition of energetic binder NC is conducive to the early reaction of B / KNO3. Fig.11 and Fig.12 The curves c, d, and e of the above graphs have an exothermic peak at around 200 °C, which is mainly due to the superposition of the thermal decomposition of NC and the decomposition of 5-AT, and it is found that the decomposition temperature of 5-AT is close to the melting point of 5-AT. In addition, the mass loss of the main reaction of the three curves is between 429-494 °C, 400-457 °C, and 380-420 °C, respectively. Compared with the ignition charge without 5-AT, with the increase of 5-AT content, the main reaction exothermic peak temperature generally shows a decreasing trend, and the main reaction temperature is advanced by 28.2, 47.5, and 72.4 °C, respectively, which indicates that the addition of 5-AT has a certain promoting effect on the reaction of B / KNO3 / NC. Curve d has a double peak, which may be caused by the redox reactions of KNO3 / 5-AT and B / KNO3, respectively.
[0061] When NC and 5-AT are added to the mixture, there is a mass loss at 200-450 ℃. With the addition of NC and the increase of 5-AT content, the mass loss of the mixture increases, but there is no obvious endothermic or exothermic peak in the DSC curve, which indicates that the decomposition process of NC and 5-AT is slow, and the decomposition products are volatilized as soon as they are formed. The addition of NC and the increase of 5-AT content advance the main reaction temperature, which may be because the heat released by the decomposition of these two substances promotes the transfer of heat in the main reaction. Table 2 shows the melting temperature of potassium nitrate, the decomposition temperature of 5-AT, the peak temperature of the main reaction and the total reaction heat of different samples. There is no significant difference between the decomposition temperature of 5-AT and the melting temperature of KNO3, but the main reaction temperature is advanced. Among the energetic film samples of B / KNO3 / 5-AT / NC with different ratios, the sample with B / KNO3:5-AT:NC=80:10:10 has the largest heat release, reaching 1397 J·g -1 , reaching 35% of the theoretical heat release. The reason why the heat release is lower than the theoretical value is mainly because the inert oxide layer shell of B and the molten products in the reaction process hinder the release of energy of the reaction system.
[0062] Table 2 Summary of DSC experimental results of B / KNO3 / 5-AT / NC energetic film samples
[0063] 3. Heat release of Al / Co3O4 / double 5-AT / NC energetic films The thermal reaction performance of the samples scraped from the Al / Co3O4 / double 5-AT / NC energetic films with different ratios was tested by DSC. The spectra are shown in Fig.13 As shown in FIG. 1 , the test conditions are: temperature range 100-800 °C; purge gas: argon; heating rate: 10 K / min; gas flow rate: 30 ml / min. Fig.13 Curve a is the DSC spectrum of Al / Co3O4: double 5-AT:NC=100:0:0; curve b is Al / Co3O4: double 5-AT:NC=90:0:10; curve c is Al / Co3O4: double 5-AT:NC=80:10:10; curve d is Al / Co3O4: double 5-AT:NC=70:20:10; and curve e is the DSC spectrum of Al / Co3O4: double 5-AT:NC=60:30:10.
[0064] from Fig.13 It can be clearly seen from curve a that the curve mainly has a huge and sharp exothermic peak and a weak endothermic peak. The starting temperature of the exothermic peak is 538.0 ℃, and the maximum heat flow is reached at 601 ℃, which mainly corresponds to the redox reaction of Al powder and Co3O4. The endothermic peak at a temperature of about 667.4 ℃ corresponds to the melting point of Al powder. Compared with curve a, curve b adds an exothermic peak at 206.3 ℃, which corresponds to the thermal decomposition process of nitrocellulose (NC). Curves c, d, and e are the spectrum curves of the film samples with double 5-AT added. Compared with the three curves, curves d and e have an obvious exothermic peak at about 260 ℃, which mainly corresponds to the decomposition peak of double 5-AT. However, curve c does not observe the decomposition exothermic peak of double 5-AT. The possible reason is that the content of double 5-AT in the film sample corresponding to this curve is low. There is no endothermic peak corresponding to the melting point of Al powder in curve d. It is possible that the endothermic peak of Al melting overlaps with the exothermic peak corresponding to the redox reaction between Al powder and cobalt tetroxide.
[0065] Table 3 shows the NC decomposition temperature, Al powder melting temperature, main reaction peak temperature and total reaction heat release of samples with different ratios. There is no significant difference between the decomposition temperature of NC and the melting temperature of Al powder, and the main reaction temperature is not much different. Among the Al / Co3O4 / double 5-AT / NC film samples with different ratios, the sample with Al / Co3O4:double 5-AT:NC=70:20:10 has the largest heat release, reaching 2286 J·g -1 , reaching 69% of the theoretical heat release. The main reason for the low heat release is that aluminum powder is easily oxidized, and its surface becomes aluminum oxide. The molten product during the reaction process hinders the release of energy of the reaction system.
[0066] Table 3 Summary of DSC experimental results of Al / Co3O4 / Dual 5-AT / NC energetic film samples
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing a Pyro-MEMS micro-charge film based on an energetic ink spin coating process, characterized in that: The steps include: 1) Substrate pretreatment: Place the copper substrate in a 40% nitric acid solution for 30 seconds to remove the oxide film on the surface of the copper substrate, then rinse with a large amount of deionized water and dry naturally for later use; 2) Ink preparation: First, nitrocellulose was added to acetone solvent and ultrasonically treated for 20 min to completely dissolve the nitrocellulose in acetone; secondly, Al / Co3O4 / double 5-AT powder or B / KNO3 / 5-AT powder was added to the above solution and stirred and ultrasonically treated to make the solution fully uniform, thereby obtaining Al / Co3O4 / double 5-AT / NC energetic ink or B / KNO3 / 5-AT / NC energetic ink; 3) Spin coating: Place the copper substrate on a spin coater, and drop the prepared Al / Co3O4 / double 5-AT / NC energetic ink or B / KNO3 / 5-AT / NC energetic ink onto the copper substrate rotating at a low speed; 4) Diffusion and volatilization: Under the high-speed rotation of the coating machine, the Al / Co3O4 / double 5-AT / NC energetic ink or the B / KNO3 / 5-AT / NC energetic ink diffuses from the middle of the copper substrate to the surrounding area and covers the entire copper substrate; during the diffusion process, accompanied by the volatilization of acetone, a stable Al / Co3O4 / double 5-AT / NC energetic film or B / KNO3 / 5-AT / NC energetic film is finally formed.
2. The method for preparing a Pyro-MEMS micro-charge film based on an energetic ink spin coating process according to claim 1, characterized in that: In step 2), the mass ratio of the substances in the Al / Co3O4 / double 5-AT / NC energetic ink is Al / Co3O4:double 5-AT:NC=70:20:10, and the mass ratio of the substances in the B / KNO3 / 5-AT / NC energetic ink is B / KNO3:5-AT:NC=80:10:
10.
3. The method for preparing a Pyro-MEMS micro-charge film based on an energetic ink spin coating process according to claim 2, characterized in that: In step 2), in the Al / Co3O4 / double 5-AT / NC energetic ink, the mass of Al is 0.25g, the mass of Co3O4 is 0.836g, the mass of double 5-AT is 0.310g, and the mass of NC is 0.155g; in the B / KNO3 / 5-AT / NC energetic ink, the mass of B is 0.27g, the mass of KNO3 is 0.73g, the mass of 5-AT is 0.125g, and the mass of NC is 0.125g.
4. The method for preparing a Pyro-MEMS micro-charge film based on an energetic ink spin coating process according to claim 3, characterized in that: In step 2), during the preparation of the Al / Co3O4 / double 5-AT / NC energetic ink, the volume of acetone added was 12 mL; during the preparation of the B / KNO3 / 5-AT / NC energetic ink, the volume of acetone added was 12 mL.
5. The method for preparing a Pyro-MEMS micro-charge film based on an energetic ink spin coating process according to claim 3, characterized in that: In step 3), the amount of Al / Co3O4 / double 5-AT / NC energetic ink or B / KNO3 / 5-AT / NC energetic ink added is 5 to 7 drops.
6. The method for preparing a Pyro-MEMS micro-charge film based on an energetic ink spin coating process according to claim 3, characterized in that: In step 4), the high-speed rotation speed of the glue machine is 3.20kr·min -1 ~3.56 kr min -1 .
7. The method for preparing a Pyro-MEMS micro-charge film based on an energetic ink spin coating process according to claim 3, characterized in that: In step 4), the rotation time of the glue spreader is 20 s.
8. The method for preparing a Pyro-MEMS micro-charge film based on an energetic ink spin coating process according to claim 5, characterized in that: In step 3), the amount of Al / Co3O4 / double 5-AT / NC energetic ink added is 5 drops, and the amount of B / KNO3 / 5-AT / NC energetic ink added is 7 drops.
9. The method for preparing a Pyro-MEMS micro-charge film based on an energetic ink spin coating process according to claim 6, characterized in that: In step 4), for Al / Co3O4 / double 5-AT / NC energetic ink, the high speed rotation speed of the coating machine is 3.20 kr·min -1 ; For B / KNO3 / 5-AT / NC energetic ink, the high speed rotation speed of the coating machine is 3.56kr·min -1 .